Analisis Deskriptif Kemampuan Motorik Halus Anak Usia Dini melalui Kegiatan Melipat Kertas di PAUD AL-AZIZIYAH - Eva Manfaatin; Nisa Munajiyah; Sakinah Fitria Zulva; Syahrazz Rifqah Rosadi (Jurnal Ilmu Pendidikan, 2026)
Fine motor skills are one of the important developmental aspects in early childhood that need to be stimulated through interesting learning activities appropriate to children’s characteristics. Based on observations at PAUD AL-AZIZIYAH, children’s fine motor skills still need to be improved because learning activities are still dominated by worksheet-based activities. This study aimed to describe the fine motor skills of early childhood through paper folding activities. This research used a quantitative approach with a descriptive research type. The research population consisted of 15 children, and the sampling technique used was total sampling. The research data were primary data obtained through observation based on the Child Development Achievement Standards (STPPA) 2022 indicators. Data analysis used descriptive statistics with ordinal scales consisting of Not Yet Developed (BB), Beginning to Develop (MB), Developing as Expected (BSH), and Developing Very Well (BSB). The results showed that 6.7% of children were in the BB category, 46.7% in the MB category, 26.7% in the BSH category, and 20.0% in the BSB category, with an average score of 2.60. These findings indicate that paper folding activities can support the development of fine motor skills in early childhood through hand-eye coordination, accuracy, and finger flexibility during learning activities